Perancangan Manajemen Acara Expert Insight Special Episode Marketing Talks “Unlocking Marketing Potential: The Power Of AI” di Telkom Corpu Tahun 2023 - Maharani Dewi, Annisya; Satrio Wijaksono, Dimas (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Event management plays an important role in the success of an event and should be implemented during its execution, especially for important events such as corporate events. This research was conducted to implement the event management design for the Expert Insight Special Episode Marketing Talks "Unlocking Marketing Potential: The Power of AI" at Telkom CorpU, a company that regularly organizes online webinar series. This research successfully attracted 306 participants, with 62.3% of 151 participants stating that they were very satisfied and 37.1% satisfied with this event. Additionally, 58% of participants liked the event based on the content provided, and 38.4% were interested in the event's speakers. This study was carried out using observation and documentation methods and utilized Goldblatt's event management theory to support the success of this event. The results of this study concluded that the event management design in this webinar successfully made the event more structured and organized in managing human resources, teamwork, and creativity.
Keywords: Expert Insight; Event; Webinar; Event Management